La syncope narrative dans Lolita de Vladimir Nabokov - Claire Maniez (Sillages Critiques)
In Nabokov’s Lolita, the rhythm of the narration can be described using the notion of syncopation. The narrator, obsessed by time, tells of his experience in terms of syncopated moments, when time is momentarily suspended or abolished. His narrative reproduces this rhythm through syntax and punctuation, as well as through the intrusion of incongruous elements which make the reader pause, thus interrupting the narrative flow. Keeping the reader alert, this syncopated rhythm participates in the creation of “aesthetic bliss” “through the satisfaction of logical recognition” which is the aim of the aesthetic experience.